Bahamas. Significant achievements 2015 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in the Bahamas during 2015 are identified, with respect to the needs and interests of the country, strengthening issues such as sustainability, innovation, financing, beekeeping, aquaponics, good agricultural practices, agribusiness, animal nutrition and in the tissue culture in laboratories. Likewise, work was done to improve meat production, in slaughterhouses, phytosanitary, through the Codex Alimentarius, in access to water and soil. Finally, support was given to the network of women producers and to the value chains of ruminants, vegetables, cassava, sweet potatoes and honey.